Apolipoprotein E polymorphisms and ischaemic stroke: a two‐center Greek study. (28th January 2014) - Chatzistefanidis, D.; Giannopoulos, S.; Spengos, K.; Vassilopoulou, S.; Vemmos, K.; Dova, L.; Vartholomatos, G.; Kyritsis, A. P.; Georgiou, I.; Markoula, S.
Abstract : Background and purpose: Apolipropotein E(apoE) is a plasma protein exhibiting three common isoforms (E2, E3, E4). Its involvement in lipoprotein metabolism may have an impact on stroke occurrence. As results in the literature are inconclusive further studies are needed to elucidate its role. Our objective was to study the role of apoE isoforms and the interplay with environmental risk factors in patients with first ischaemic stroke occurrence in the Greek population. Methods: Three hundred and twenty‐nine patients with first‐ever ischaemic stroke were included in our study. Strokes of cardioembolic origin and patients with autoimmune or prothrombotic syndromes were excluded. A control group of 361 subjects with no stroke history were also included in our study. Risk factors (hyperlipidemia, hypertension, diabetes mellitus and smoking) were assessed. ApoE alleles were determined in all subjects participating in the study. Results: Genotype ε3/ε3 was found to have a protective role against stroke occurrence compared with other genotypes (odds ratio 0.674, 95% confidence interval 0.480–0.946) especially in the female patient subgroup. In multivariate analysis after adjustment for age, body mass index (BMI), hypertension, dyslipidemia, diabetes mellitus and smoking, the role of genotype was limited and outweighed by risk factors in both genders. No association between apoE alleles and BMI, cholesterol, triglycerides or high‐density lipoprotein plasma levels was noted. Conclusions: Our study was indicative of a protective role of the ε3/ε3 genotype, especially in female patients. However, risk factors such as age, BMI, hypertension, dyslipidemia, diabetes mellitus and smoking have a strong impact on stroke occurrence and outweigh the protective role of the ε3/ε3 genotype. Abstract : Clickhere to view the accompanying paper in this issue.